Basics of solitons - Sinha, D. K. (Dilip Kumar), 1940- (Mathematics of mathematical sciences., 1982)
On solitons, mathematical theory, and its applications in applied mathematics and physics; papers presented at a seminar, Jadavpur University, Calcutta.